CYP2C19 pharmacogenetics versus standard of care dosing for selecting antiplatelet therapy in patients with coronary artery disease: A meta‐analysis of randomized clinical trials. Issue 7 (7th November 2018) - Kheiri, Babikir; Osman, Mohammed; Abdalla, Ahmed; Haykal, Tarek; Pandrangi, Pranay V.; Chahine, Adam; Ahmed, Sahar; Osman, Khansa; Bachuwa, Ghassan; Hassan, Mustafa; Bhatt, Deepak L.
Abstract: Objectives: This study aimed to evaluate the efficacy and safety of personalized genotype‐guided selection of antiplatelet therapy versus standard of care in patients undergoing percutaneous coronary intervention (PCI). Background: Clopidogrel is the most frequently used P2Y12 receptor antagonist in patients with coronary artery disease. However, genetic variations of clopidogrel are associated with inter‐individual response variability which could limit its efficacy. Methods: Electronic databases were searched for all randomized clinical trials (RCTs) evaluating genotype‐guided therapy versus standard of care in patients undergoing stent implantation. Aggregated risk ratios (RRs) and 95% CIs were calculated using a random‐effects model. Results: We included 6 RCTs with a total of 2, 371 patients. When compared with standard of care, the use of genotype‐guided therapy did not significantly reduce major adverse cardiovascular events (MACE) (RR 0.67; 95% CI: 0.35–1.27; P = 0.22). However, MACE was significantly reduced in the subset of trials which enrolled only acute coronary syndromes (ACS) ( P < 0.01). In addition, there was a significant reduction in myocardial infarction in the genotype‐guided group (RR 0.44; 95% CI: 0.28–0.70; P < 0.01; I 2 = 0%). Other clinical outcomes were not significantly different: cardiovascular mortality (RR 0.68; 95% CI: 0.27–1.74; P = 0.42), stroke (RR 0.62; 95% CI: 0.23–1.65; P = 0.34), stent thrombosis (RR 0.37; 95% CI: 0.13–1.06; P = 0.06), and bleeding (RR 0.68; 95% CI: 0.43–1.06; P = 0.09). Conclusion: In patients undergoing stent implantation, MACE with genotype‐guided therapy was not significantly reduced; however, there was a signal towards reduction of MACE in ACS patients, as well as a lower rate of MI, though this will require further confirmation in adequately powered trials.